Transformasi Multipel dalam Pengembangan Seni Kuda Kepang - Kiswanto Kiswanto (Institut Seni Indonesia Yogyakarta, 2019)
This article aims to discourse the perspectives of multiple transformations in the practice of developing performing art of kuda kepang at Turonggo Seto Mardi Utomo group in Boyolali, Central Java. The study of multiple transformations has long been evolving in design and architecture research, but the perspective is rarely encountered in performing arts research which on average still views transformation as a linear or multi-linear process of change. Multiple transformations describe a condition of change made by multiplying or doubling the shape of the kuda kepang art (by taking the same essence, core, or fibre of its structure) into various kinds. The multiplication shows a process of creative development that is triggered by two factors, namely the development of aesthetic and market needs.Keywords: kuda kepang; multiple transformations; traditions; creativity; markets